Laguerre Collocation Method for Solving Fredholm Integro-Differential Equations with Functional Arguments - Burcu Gürbüz; Mehmet Sezer; Coşkun Güler (Journal of Applied Mathematics)
Laguerre collocation method is applied for solving a class of the Fredholm integro-differential equations with functional arguments. This method transforms the considered problem to a matrix equation which corresponds to a system of linear algebraic equations. The reliability and efficiency of the proposed scheme are demonstrated by some numerical experiments. Also, the approximate solutions are corrected by using the residual correction method.